Ultraviolet-Visible Light-Sensitive High Surface Area Phosphorous-Fluorine-Co-Doped TiO2 Nanoparticles for the Degradation of Atrazine in Water - Khan, J.A.; Han, C.; Shah, N.S.; Khan, H.M.; Nadagouda, M.N.; V. Likodimos; P. Falaras; O'Shea, K.; Dionysiou, D.D. (Environmental Engineering Science, 2014)
Conventional titanium dioxide (TiO2) materials can be activated only by ultraviolet (UV) light, which is only 4-5% of the whole solar spectrum. As a result, visible light (vis)-active TiO2-based photocatalysts have recently received significant attention in the field of TiO2 photocatalytic treatment and purification of water and air. This study reports the preparation of UV-visible light-active phosphorous (P)-doped, fluorine (F)-doped, and PF-co-doped anatase TiO2 nanoparticles via an innovative sol-gel method. Prepared nanoparticles were characterized by UV-vis diffuse reflectance spectroscopy, X-ray diffraction analysis, Raman spectroscopy, high-resolution transmission electron microscopy, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy (FTIR), and porosimetry analysis. Synthesized materials exhibited improved structural properties, including high surface area, small crystallite size, reduced band gap energy, mesoporous structure, and high porosity. Due to doping with P and F, light absorption of TiO2 in the visible light region was efficiently enhanced with effective band gap energy of 2.70 eV. Brunauer-Emmett-Teller (BET) surface area for PF-co-doped, P-doped, F-doped, and reference TiO2 nanoparticles was 212.0, 175.0, 88.8, and 79.7 m2/g, respectively. PF-co-doped TiO2 showed the highest photocatalytic degradation of atrazine, which could be attributed to the beneficial effects including small crystallite size, high BET surface area, and light absorption in UV-visible region, induced by co-doping of TiO2 with P and F. Finally, reaction intermediates were determined, which confirms the photocatalytic degradation of atrazine using the synthesized catalysts under UV-visible light illumination. © Copyright 2014, Mary Ann Liebert, Inc. 2014.